Dissolved iron-binding organic ligand characteristics from the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) project, Utqiaġvik, Alaska, 2021 ... - Buck, Kristen; Artigue, Lise; Whitmore, Laura; Aguilar-Islas, Ana (NSF Arctic Data Center, 2024)
This dataset includes the concentrations and conditional stability constants of iron-binding organic ligands in samples collected during an extension study of the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) project and measured by competitive ligand exchange-adsorptive cathodic stripping voltammetry (CLE-AdCSV). These samples originated from a spring melt field campaign conducted in Utqiaġvik, Alaska. This campaign was designed when the MOSAiC expedition could no longer accommodate spring melt trace metal work. The melt season was a key period of our effort during MOSAiC and necessary for addressing our proposed hypotheses. Using facilities in Utqiaġvik hosted by Ukpeaǵvik Iñupiat Corporation (UIC), we studied sea ice processes during the spring melt cycle from April – June of 2021. Four UAF Scientists participated in the field campaign. During that time, sea ice, snow and water samples were obtained from homogenous, flat, landfast ice at high (2-3 times a week) temporal ...